Professor Challenger and his lost neolithic world : the compelling story of Alexander Thom and British Archaeoastronomy - Mackie, Euan W. (Access archaeology., 2020)
"The book is semi-autobiographical in style charting Dad's investigation of Thom's theories across a number of key Neolithic sites from Kintraw to Stonehenge and finally Orkney. It also maps his own perspective of the changing reception to Thom's ideas by the archaeological profession from initial curiosity and acceptance to increasing scepticism. This healthy and necessary diversion of views energised Dad well into his retirement to continue researching in the area, conducting painstaking field investigations from which to inductively infer the astronomical abilities of the Neolithic 'priesthood'. The first six chapters are historical summaries of the various strands of evidence from key Neolithic sites across the UK and Ireland with the compelling evidence of the Ness of Brodgar added as an appendix. The final chapter was Dad's endeavour at adding some contemporary references and brought a more optimistic tone to the acceptance of Thom's ideas. Unfortunately ill-health prevented him from editing this final chapter so we have done this for him to enable publication" --